Bedingungsloses Grundeinkommen und Solidarisches Bürgergeld - mehr als sozialutopische Konzepte - Straubhaar, Thomas (Hamburg University Press, 2008)
Thomas Straubhaar and Ingrid Hohenleitner outline in this publication the model of an unconditional basic income grant. They show that it is affordable for Germany. They see the basic income as an opportunity to reorganize the government budget and the welfare state in a sustainable way for future generations. They show that there could be particularly in the field of low income jobs new jobs be created in the amount of up to 1.17 million full-time positions. Michael Opielka sees in the model by Althaus "a kind of a combination wage for all". A part of the national income will be evenly distributed. With a "mixture of pragmatism and idealism", the basic income create a "true" labor market, while rewarding part-time work and securing volunteering and educational phases. The basic income proposed by Dieter Althaus would be an important step on the path to greater social solidarity, to more subsidiarity, and tomore (social) justice. This is the conclusion reached by Michael Schramm. Also the system of social protection would be based on an economically sound basis and a revitalization of the labor market and entrepreneurial forces would follow.